Association of Genetic Variation of Sodium Taurocholate Cotransporting Polypeptide with Chronic Hepatitis B Virus Infection - Li, Na (Mary Ann Liebert, Inc., 2014)
Background: Sodium taurocholate cotransporting polypeptide (NTCP) plays an important role in the enterohepatic circulation of bile acids and hepatocyte function and was recently proposed to be a functional receptor for hepatitis B virus (HBV). Objective: This study investigated the association of the functional polymorphism c.800C>T (p.S267F) (rs2296651) of the NTCP gene with HBV infection. Methods: The study included 244 patients with chronic HBV infection, 76 HBV infection resolvers, and 113 healthy controls. The polymorphism was genotyped using the polymerase chain reaction–restriction fragment length polymorphism method. Results: The distribution of the genotype and allele frequency of rs2296651 polymorphism was significantly different among the HBV patients, HBV infection resolvers, and healthy controls (p=0.034 and p=0.039, respectively). The frequency of genotype CT in HBV patients was significantly higher than that in healthy controls (11.9% vs. 4.4%, p=0.026, odds ratios [OR]=2.913, 95% confidence intervals [95% CI]=1.097–7.738). The frequency of allele T in HBV patients was also significantly higher than that in healthy controls (5.9% vs. 2.2%, p=0.029, OR=2.793, 95% CI=1.067–7.312). The frequency of genotype CT and allele T in HBV patients was higher than that in HBV infection resolvers although the difference was not significant. The genotype and allele frequency between infection resolvers and healthy controls and between HBV patients with different clinical diseases had no significant difference. Conclusion: These findings suggest that the rs2296651 polymorphism may predispose the susceptibility to and chronicity of HBV infection.